Chemometric Approaches for the Zoning of Pinot Noir Wines from the Casablanca Valley, Chile - Yanez-Catalan, L (Elsevier Ltd, 2011)
The Casablanca valley of Chile is one of the youngest wine producing areas of the country. This valley is of interest to national and international wine producers and consumers because of its unique climate. However, no systematic studies have been performed to evaluate differences in the climate inside the valley. In this work, the chemometric zoning of the Casablanca valley is assessed for the first time using samples of Pinot noir produced in two sub-zones. The samples were chemically characterised by UV-VIS spectroscopy, anthocyanin profiles and mineral element profiles. Data were analysed using the multivariate tools PCA, LDA, SIMCA and PLS-DA. The best results were obtained by combining all chemical data (R2 > 98%, Q2 ? 0.5). No differences were detected among the applied statistical procedures. Finally, the results of this preliminary survey yield promising scientific evidence of two existing sub-zones within the Casablanca valley, the "Zona Alta" and the "Zona Baja", in agreement with the previous opinion of oenologists. © 2011 Elsevier Ltd. All rights reserved.